2020
DOI: 10.3390/cancers12102821
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Fusion Imaging and Contrast-Enhanced Imaging (CT/MRI–CEUS) in Oncology

Abstract: Fusion imaging depicts an innovative technique that facilitates combining assets and reducing restrictions of advanced ultrasound and cross-sectional imaging. The purpose of the present retrospective study was to evaluate the role of fusion imaging for assessing hepatic and renal lesions. Between 02/2011–08/2020, 92 patients in total were included in the study, of which 32 patients had hepatic lesions, 60 patients had renal lesions. Fusion imaging was technically successful in all patients. No adverse side eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 72 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…Moreover, by means of fusion imaging previously acquired data from CT and MRI scans may be integrated and processed in up-to-date ultrasound devices, allowing for real-time computerized fusion of cross-sectional images with ultrasound images in a real-time manner. Fusion imaging may allow to further evaluate focal renal lesions, particularly of previously as indeterminate described lesions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by means of fusion imaging previously acquired data from CT and MRI scans may be integrated and processed in up-to-date ultrasound devices, allowing for real-time computerized fusion of cross-sectional images with ultrasound images in a real-time manner. Fusion imaging may allow to further evaluate focal renal lesions, particularly of previously as indeterminate described lesions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contrast-enhanced ultrasound is an increasingly utilized imaging modality with a high diagnostic accuracy for characterizing renal lesions [ 28 , 29 , 30 ]. Previous studies demonstrated that CEUS is more sensitive in detecting the contrast-enhancement of cystic renal lesions than contrast-enhanced CT and MRI [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contrast-enhanced ultrasound is an increasingly utilized imaging modality with a high diagnostic accuracy for characterizing renal lesions [28][29][30]. Previous studies…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was recently demonstrated that the combination of CEUS with previously acquired CT or MRI data in the context of advanced Fusion Imaging could help to decipher initially as indeterminate classified hepatic lesions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%